Jogo Mobile para Aprendizagem Lúdica de Língua Inglesa para Pessoas com Deficiência Visual - Santos, Valmir Vinicius; Pereira, Claudia (Proceedings of the Regional School on Computing of Bahia, Alagoas, and Sergipe (ERBASE), 2020)
Despite the great evolution of the learning and teaching methods, initiatives that seek to promote accessibility are still timid. In that sense, this article proposes a mobile game for english learning focused on people with visual impairments. Aimed to young audiences, the application uses songs as a means for build knowledge. Composed of two challenges, the game has an engine to describe text in audio, besides the accessible visual interface. The project development has been conducted based on inputs obtained through Sistematic Mapping. Besides other methodological procedures, this article will also describe the implementation process, the game dynamics and preliminary results.